Expected learning outcomes by New Media usage for Senior secondary school students-A Structural Equation Modelling perspective - et. al., Prof.(Dr) Deependra Sharma, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the era of challenges and irrespective of any education level, the education sector has attained new paradigm Post Covid19 situation. The school education as well as higher education has undergone a massive transformation due to the usage of New Media technology for formal as well as informal learning. The educators have to use any apply the never before used technologies and pedagogies. This study includes solution to the research question and testing of hypothesis related to the impact of New Media usage on the expected learning outcomes related to study. This was followed by hypotheses explained on the basis of Sub-hypotheses. These hypotheses pertain to the relationship between New Media usage and the expected learning outcomes.The exploratory research study titles as New Media usage and expected learning outcomes for Senior secondary school students is based on a Structural Equation Modelling(SEM) perspective using PLS-SEM analysis tool. The study also focuses on identifying expected learning outcomes in term of Academic and non-academic areas of school education based on the premises of developing holistic development. The expected impact explained in terms of the significant impact due to the usage of New Media technology and devices There is a significant impact due to New Media usage explained in terms of expected learning outcomes on the basis of Academic and non-Academic area. These learning outcomes factors are defined as Scholastic Gratifications, Academic Achievement, Confidence development, Social Wellbeing, Indoor Gaming, Virtual Learning, Learning by Modern Technology .